Finishing properties of laptop table from Kelempayan (neolamarckia cadamba) wood / Engku Syahmi Arif Engku Ahmad Fakri - Engku Ahmad Fakri, Engku Syahmi Arif (2014)
Finishing is the final process in furniture manufacturing. The function of finishing process is to give protection and good appearance on product surface. Finishing consist of two stages which is pre-finish and finish. Pre-finish is preparation of surface product before applying the coating material. It is need to keep the product away from dust, dirt, oil and any unwanted particle.. This preparation using sandpaper that also give smoothness to product surface. Sandpaper comes in various grit that provides different roughness on surface. In this study, two types of grit sandpaper use which is 120 and 320 grit by using acid catalyst (AC) clear as coating material. The results show that 320 grit sandpaper gives better results for the finishing properties. Then, three different technique applying coating material are use which are 2 layer. 4 layer and 6 layer. The results obtained that 6 layer of coating material produced best result.